#### Answer

$ -32 x^{15} y^{10}$

#### Work Step by Step

$(-2x^3y^2)^5 = (-2)^5(x^3)^5(y^2)^5 = -32 x^{15} y^{10}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$ -32 x^{15} y^{10}$

$(-2x^3y^2)^5 = (-2)^5(x^3)^5(y^2)^5 = -32 x^{15} y^{10}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.